Measuring and Monitoring Effects of Sustainable Development in the European Union - Urbaniec, Maria (European Journal of Sustainable Development, 2016)
Abstract Sustainable development is considered as the central model of socio-economic development as well as an overarching principle of global environmental policy. Taking measures and effective policy in strategic areas require statistical information from various fields. An important tool in this context is monitoring the progress on implementation of sustainable development. The aim of the article is to analyze the conditions and principles for the measurement of sustainable development in the EU and to assess progress in implementing the European Strategy for Sustainable Development. On the basis of available statistical data it is possible not only to measure the progress and evaluate the effectiveness of policies and programs of the European Union, but also to support decision making at the political level in terms of economic, social and environmental developments. Keywords: sustainable development, sustainable development strategy, indicator; measuring, progress monitoring